2002
DOI: 10.1038/sj.npp.1300063
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Amphetamine-Induced Behavioral Sensitization after Short- and Long-Term Withdrawal Periods: Participation of μ- and δ-Opioid Receptors

Abstract: Repeated amphetamine administration results in behavioral sensitization, an enduring behavioral transformation expressed after short and long periods of withdrawal. To investigate the participation of the opioid system in amphetamine-induced behavioral sensitization, we studied the effect of naloxone, an opioid receptor antagonist, on the expression of behavioral sensitization tested after short-(2 days) and long-term (14 days) withdrawal periods. In addition, using quantitative competitive RT-PCR, we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 48 publications
3
26
1
Order By: Relevance
“…A previous study in rats, which was similar to this experiment, found that naloxone (5 mg/kg) did not modify the expression of behavioral sensitization after 2 days of abstinence, but it completely blocked the expression when tested after 14 days of abstinence [27]. Although the inhibitory effects of 10 and 20 mg/kg of NAT on day 21 appeared to be more potent than those on day 11, the discrepancies may have resulted from differences in subjects, drugs, or experimental conditions used in the two studies.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A previous study in rats, which was similar to this experiment, found that naloxone (5 mg/kg) did not modify the expression of behavioral sensitization after 2 days of abstinence, but it completely blocked the expression when tested after 14 days of abstinence [27]. Although the inhibitory effects of 10 and 20 mg/kg of NAT on day 21 appeared to be more potent than those on day 11, the discrepancies may have resulted from differences in subjects, drugs, or experimental conditions used in the two studies.…”
Section: Discussionsupporting
confidence: 79%
“…This up-regulation of opioid receptors has been shown to accompany supersensitivity to opioid agonists and is an indication of their functional relevance [48]. Moreover, repeated treatment with AMPH or METH was found to increase not only the mRNA levels of μ-opioid receptors in the VTA and NAcc [27] but also the dopamine releasing effects of μ-opioid receptor agonist [55]. This suggested that the alterations in μ-opioid receptors are functionally involved.…”
Section: Discussionmentioning
confidence: 82%
“…However, inherent to application of classic knockout strategies and hence lack of a specific gene from gestation, the possibility that for example d-opioid receptors have compensated for the loss of m-opioid receptors in this case cannot be ruled out. Retained cocaine-induced behavioral sensitization for m-opioid receptor knockout mice is not in agreement with previous studies, which suggested a role of m-opioid receptors in psychostimulant sensitization (Sala et al, 1995;Magendzo and Bustos, 2003;Yoo et al, 2003). Therefore, a subsequent experiment was performed to elucidate the role of m-opioid receptors in cocaine-induced sensitization.…”
Section: Cocaine-induced Behavioral Sensitizationsupporting
confidence: 45%
“…A role of m-opioid receptors in psychostimulant sensitization was suggested first of all by impaired cocaineinduced sensitization after NTX co-administered with cocaine (Sala et al, 1995) and also by findings of two recent studies. Expression of mRNA encoding m-and d-opioid receptors was increased in the VTA of amphetaminesensitized rats (Magendzo and Bustos, 2003). Another study dealt with cocaine-induced behavioral sensitization in mice with a targeted deletion of exons 2 and 3 of the m-opioid receptor gene.…”
Section: Cocaine-induced Behavioral Sensitizationmentioning
confidence: 99%
“…Doudet and Holden (2003) also reported that MA competed for the same D2 receptors as the dopamine antagonist, raclopride. Magendzo and Bustos (2003) demonstrated in rats that acute MA exposure resulted in increased transcription of mu opioid receptor and delta opioid receptor in the ventral tegmental area, which corresponded with an acute sensitization to MA. These results implicate the indirect striatopallidal pathway because of the colocalization of enkephalin (via the mu receptor) and GABA.…”
Section: Motor Dysfunction Following Ma Preclinical Studiesmentioning
confidence: 97%